X patrystyczne dni augustiańskie - Longosz, Stanisław (Vox Patrum, 1981)
Report from the patristic scientific conference at the "Augustinianum" Patristic Institute on the subject: "The Old Testament in the ancient church of the first three centuries", which took place on May 7-9, 1981 in Rome.